Madagascar : Selected Issues and Statistical Annex. (IMF Staff Country Reports; Country Report, 1996)
This Selected Issues paper and Statistical Annex analyzes the inflation and monetary policy in Madagascar during the 1990s. The paper highlights that in 1995, Madagascar's inflation performance was somewhat disappointing, although 12-month price increases slowed from 60 percent at end-1994 to 38 percent at end-1995. The paper provides selected stylized facts concerning money and prices. A simple model of price formation in a small open economy is presented. The paper also addresses issues in estimating long-term relationships, discusses the results, and presents a forecast for inflation in 1996.